BUDDHIST INFLUENCE ON WINDSCREEN LITERATURE: A STUDY ON STICKER PHRASES POSTED ON THE THREE WHEEL TAXIES IN SRI LANKA - Karunarathna (B.A. Peradeniya), Lokeshwari Sandamali (European Scientific Journal, ESJ, 2014)
In this paper, we focused on the Buddhist attitudes conveyed through sticker phrases posted on TWTs in Sri Lanka. The main factor which has been studied in this research survey is the influence of Buddhist attitudes upon the TWT community in Sri Lanka in their selection and posting the above mentioned literature pieces on their taxies. For this purpose, we have gathered a collection of 2291 phrases from 831 TWTs in fifteen towns in Kandy, Colombo, Anuradhapura, and Matara districts representing four provinces out of nine. Only Sinhala and English phrases were considered. We found 619 relevant sticker phrases which conveyed an influence of Buddhist attitudes and were categorized into twelve themes. The analysis of results was done both quantitatively and qualitatively. Impermanency, karma, samsara, nirvana, merits and sins, power of human minds, gods and Mara were commonly used Buddhist concepts among these phrases. ‘Buddhist benedictory sentences’ were the most popularly used theme and Kandy had shown the highest frequency of using the shreds with Buddhist influence.